Proniosomes for Oral Delivery of Aceclofenac: Impact of Paddle Versus Dialysis Methods on In vitro-in vivo Correlation (IVIVC) Predictions - Sammour, Rana M. F.; Almurisi, Samah H.; Taher, Muhammad; Shahiwala, Aliasgar (Drug Delivery Letters, 2023)
Background: This study aims to assess the suitability of in vitro drug release methods, dialysis and paddle methods for predicting in vivo behaviour of Aceclofenac (ACE) proniosomes. Methods: ACE proniosomes are prepared using different carriers: glucose, maltodextrin and mannitol by the slurry method. The release studies of ACE proniosomes formulations were performed using the paddle, and dialysis methods while in vivo studies were performed in albino rats. Graphical presentation, model-dependent and model-independent approaches were applied to compare two dissolution methods. Results: More than 70% of the drug was released from ACE proniosomes over 60 min by paddle method while not more than 5% was released in the same period by dialysis method. The paddle method provides a reproducible and faster release, whereas poor drug release occurred with the dialysis method. For the paddle method, lower values of similarity factor (f2) and greater differences in the dissolution efficiency (DE) amongst different formulations and in comparison, to that of the pure drug indicates that it is a more discriminative method compared to dialysis. The paddle method also illustrated high regression coefficients (r2) of 0.81, 0.998 and 0.975 for FN1, FN2, and FN3, respectively for level A IVIVC, while poor or no relation (r2 0.1) was detected in the case of dialysis method. Conclusion: Based on the results, the paddle method is concluded to be the more suitable method compared to the dialysis method for in vitro drug release studies of a novel dosage form such as proniosomes.
Keywords: in vitro in vivo correlation